HUBUNGAN DAYA LEDAK OTOT TUNGKAI DENGAN KECEPATAN TENDANGAN T PADA SISWA PERGURUAN SILAT WALET PUTI PEKANBARU - Indah Rahmatu Dewi; Ramadi '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem in this research was is still lack of speed T kick on students silat walet puti pekanbaru. It is suspected lack of leg muscle explosive power at the time of the T kick. The purpose of this study to determine the correlation of leg muscle explosive power with the speed of a T kick. This is correlational study that aimed to know corelation between independent and dependent variabels. After that, conducted data normality test by Liliefors test with significant level α = 0.05, and the result for normality test of variable X, L0maks ((0,121) <Ltable(0,258), the normality test of variable Y, L0maks (0,208)<Ltable (0,258), in other words the distribution of the data was normal. Then continued to found r used product moment correlation analysis, if rresult > rtable so it was have significant correlation. The result of this research showed: it was significant correlation between leg muscle explosive power with the speed of a T kick, rresult ((0,703) > rtable (0,666). The conclusion was have significant correlation between leg musle explosive power with speed T kick in pencak silat athletes sons walet puti Pekanbaru.Keywords: Explosive power leg muscle, Speed T kick